Dobra Bosna (trans. Bosnia the Good: Tolerance and Tradition) - Mulalic, Muhidin (Jurnal Usuluddin, 2002)
The author started by defining the 1990’s Bosnian conflict through analyzing its roots and causes. He later presented an excellent discussion on the present predicament of the Bosnian people in the light of ideological, metaphysical (tasawwuf), religious and historical perspectives. Accordingly, his contribution is indispensable for those who wish to have a better understanding of Serbian, Croatian and even European at tempts to wipe out the Bosnian multi-ethnic and multi-religious identity.